1988
DOI: 10.1128/mcb.8.5.2214
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic growth factors activate the tyrosine phosphorylation of distinct sets of proteins in interleukin-3-dependent murine cell lines.

Abstract: By immunoblotting with antibodies for phosphotyrosine, we have demonstrated that the hematopoietic growth factors interleukin-2, interleukin-3, interleukin-4, and granulocyte-macrophage colony-stimulating factor stimulate the tyrosine phosphorylation of specific sets of proteins in murine hematopoietic progenitor cell lines. The stimulation of tyrosine phosphorylation is a receptor-dependent transient event. The effect of these hematopoietic growth factors on protein tyrosine phosphorylation was not mediated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…A set of proteins is phosphorylated rapidly on tyrosine residues after the addition ofthese growth factors (21)(22)(23)(24)(25) (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…A set of proteins is phosphorylated rapidly on tyrosine residues after the addition ofthese growth factors (21)(22)(23)(24)(25) (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…The PI-PLC-activated CD3/Ti stimulation requires tyrosine phosphorylation (37), and CD45 ligation prevents tyrosine phosphorylation of specific substrates during either CD2-or CD3-mediated activation (17). Stimulation of some of the receptors studied in the present report, including those for IL3, GM-CSF, and MGF, induces rapid tyrosine phosphorylation of cellular substrates (38). Phospholipase C y can be activated as one of these substrates by epidermal growth factor and platelet-derived growth factor receptors (39,40) .…”
mentioning
confidence: 99%
“…They exert their effects on target cells through specific receptors, and c subunits, that are regarded as members of the Jak family (Ihle & Kerr 1995). Although the GM-CSF and IL-3 receptors do not contain intrinsic tyrosine kinase activity, many cellular proteins are rapidly tyrosine phosphorylated in response to GM-CSF and/or IL-3 (Morla et al 1988, Sorensen et al 1989, Isfort & Ihle 1990, Duronio et al 1992. It has been shown that the human c subunit mediates activation of Jak2 kinase (Darnell et al 1994, Quelle et al 1994, Rothman et al 1994 and Ras, Raf-1, and mitogen activated protein kinase (MAPK) (Sato et al 1993.…”
Section: Introductionmentioning
confidence: 99%